Analog Coherent Detection for Energy Efficient Intra-Data Center Links at 200 Gbps Per Wavelength - Hirokawa, Takako; Pinna, Sergio; Hosseinzadeh, Navid; Maharry, Aaron; Andrade, Hector; Liu, Junqian; Meissner, Thomas; Misak, Stephen; Movaghar, Ghazal; Valenzuela, Luis A.; Xia, Yujie; Bhat, Shireesh; et al. (Journal of lightwave technology, 2021)
As datacenters continue to scale in size, energy efficiency for short reach (<; 2 km) links is a major factor for networks that may connect hundreds of thousands of servers. We demonstrate that links based on analog coherent detection (ACD) offer a promising path to simultaneously achieving significantly larger link budgets and improved link energy efficiency. A complete analysis is presented that considers the power consumption of all the photonic and electronic components necessary to realize an ACD link architecture based on 50 Gbaud (GBd) quadrature phase-shift keying (QPSK) signaling combined with polarization multiplexing to achieve 200 Gb/s/λ. These links utilize receivers that incorporate an optical phase-locked loop (OPLL) to frequency- and phase-lock the local oscillator (LO) laser to the incoming signal. QPSK modulation offers compelling advantages both in achievable link budget and in energy efficiency. Indeed, low-complexity electronics based on limiting amplifiers can be used as opposed to the linear front-ends, A/D converters, and digital signal processing (DSP) required for higher-order QAM or PAM formats. Our analysis indicates that links with 13 dB of unallocated budget operating at error rates of <; 10 -12 can be achieved and is compatible with higher error rates that require forward error correction (FEC). We present a comparison of silicon and InP platforms and evaluate both traveling-wave and segmented modulator designs, providing an illustration of the wide design space before converging on the most promising architectures that maximize energy efficiency and minimize laser power. We establish the theoretical potential to achieve picojoule-per-bit energy efficiency targets.